A review of μ-τ flavor symmetry in neutrino physics. (20th June 2016) - Xing, Zhi-Zhong; Zhao, Zhen-Hua
Abstract: Behind the observed pattern of lepton flavor mixing is a partial or approximate μ - τ flavor symmetry—a milestone on our road to the true origin of neutrino masses and flavor structures. In this review article we first describe the features of μ - τ permutation and reflection symmetries, and then explore their various consequences on model building and neutrino phenomenology. We pay particular attention to soft μ - τ symmetry breaking, which is crucial for our deeper understanding of the fine effects of flavor mixing and CP violation.